Augmented reality performance: A site-specific volumetric video experience of Samuel Beckett's Play - O'Dwyer, Néill; Johnson, Nicholas; Young, Gareth (Bloomsbury Methuen Drama, 2025)
This chapter documents Augmented Play (2019), an augmented reality reinterpretation of Samuel Beckett’s Play and the final work in the three-year XR Play Trilogy (following a webcast and a VR version). It is written as a reflective practice account that explains the project’s artistic rationale, production pipeline, and evaluative outcomes. The chapter details how offline volumetric video assets of the three characters were captured and computationally reconstructed (via an intensive multi-camera, green-screen workflow) and then deployed within an AR, site-specific experience. Unlike VR, the AR version uses the real architectural setting as scenography: audiences move through a chosen venue and encounter the characters as co-present digital figures, with narrative progression driven by a simple interaction rule—characters speak when looked at, and pause when gaze shifts away. The final section analyses subject-matter-expert feedback, balancing enthusiasm about AR’s captivation and pedagogical potential with concerns about liveness, accessibility/cost, operational complexity, and surveillance politics.
Extended Reality Performance: Scenographic Practice in Virtual and Augmented Reality Technologies
PUBLISHED
London
Keywords: Creative Arts Practice; Creative Technologies; Digital Engagement; Digital Humanities; Arts in Education; Digital Media; Dramatic/Theatre Arts; Film Studies; Human computer interactions; Media Arts; Performing Arts; Samuel Beckett; Other; Education; Social participation